2021
DOI: 10.1007/s11682-021-00484-x
|View full text |Cite
|
Sign up to set email alerts
|

REPIMPACT - a prospective longitudinal multisite study on the effects of repetitive head impacts in youth soccer

Abstract: Repetitive head impacts (RHI) are common in youth athletes participating in contact sports. RHI differ from concussions; they are considered hits to the head that usually do not result in acute symptoms and are therefore also referred to as “subconcussive” head impacts. RHI occur e.g., when heading the ball or during contact with another player. Evidence suggests that exposure to RHI may have cumulative effects on brain structure and function. However, little is known about brain alterations associated with RH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In the USA, the DIAGNOSE CTE and Concussion Legacy Foundation (91) projects are currently investigating the association between contact sports players (NFL, rugby, hockey, soccer) and CTE (34). A prospective study in the UK (HEADING) and the multinational REPIMACT study will examine a potential link between soccer players and dementia (84,85). The results of these studies will be highly influential guiding the future regulation of all types of contact sports.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, the DIAGNOSE CTE and Concussion Legacy Foundation (91) projects are currently investigating the association between contact sports players (NFL, rugby, hockey, soccer) and CTE (34). A prospective study in the UK (HEADING) and the multinational REPIMACT study will examine a potential link between soccer players and dementia (84,85). The results of these studies will be highly influential guiding the future regulation of all types of contact sports.…”
Section: Discussionmentioning
confidence: 99%
“…Highlights of this consortium are featured in an article in this issue. The REPIMPACT Consortium, started in 2017, focused on adolescent soccer players, including neuroimaging, blood biomarkers, and neurobehavioral assessments at 6 sites across the European Union and Israel (Koerte et al, 2021).…”
Section: Funding Trendsmentioning
confidence: 99%
“…Multimodal studies have a critical role to play, however, in this review, we identified a limited number of studies using multiple methods to date. Therefore, it is recommended that future studies combine biofluid markers with other methods that can reveal the mechanisms of pathology following RSHI exposure, such as combining neuro-imaging and sensitive and informative measures of cognition and motor control [18], and that imaging methods are multi-modal (e.g., [134,135]).…”
Section: Future Researchmentioning
confidence: 99%